Preventing child mental health problems in southeastern Europe: Feasibility study (phase 1 of MOST framework). Issue 3 (7th September 2021) - Jansen, Elena; Frantz, Inga; Hutchings, Judy; Lachman, Jamie; Williams, Margiad; Taut, Diana; Baban, Adriana; Raleva, Marija; Lesco, Galina; Ward, Cathy; Gardner, Frances; Fang, Xiangming; et al.
Abstract: The prevalence of child emotional and behavioral problems is an international problem but is higher in low‐ and middle‐income countries (LMIC) where there are often less mental health supports for families. Parenting programs can be an effective means of prevention, but must be low‐cost, scalable, and suitable for the local context. The RISE project aims to systematically adapt, implement, and evaluate a low‐cost parenting program for preventing/reducing child mental health problems in three middle‐income countries in Southeastern Europe. This small pre–post pilot study is informed by the Reach, Efficacy, Adoption, Implementation, and Maintenance (RE‐AIM) framework and tested the feasibility of the intervention, the implementation, and evaluation procedures: Phase 1 of the three‐phase Multiphase Optimization Strategy (MOST) for program adaptation. Local facilitators delivered the Parenting for Lifelong Health (PLH) for Young Children program to parents of children aged 2–9 in North Macedonia, the Republic of Moldova and Romania in 2018. Parents completed assessments pre‐ and post‐program. Results demonstrated positive pre–post change for participating families ( N = 140) on various outcomes including child externalizing and internalizing symptoms and parenting behavior, in all three countries, all in the expected direction. Program participation was associated with positive outcomes in participating families. Based on the experiences of this pilot study, we outline the practical implications for the successful implementation of parenting programs in the three countries that will inform our next study phases, factorial experiment, and RCT. Resumen: El predominio de los problemas emocionales y conductuales de los niños es un problema internacional, pero es mayor en los países de ingresos bajos y medios donde generalmente hay menos asistencia para la salud mental de las familias. Los programas de crianza pueden ser un medio de prevención eficaz, pero deben ser de bajo costo, escalables y adecuados para el contexto local. El proyecto RISE tiene como finalidad adaptar, implementar y evaluar sistemáticamente un programa de crianza de bajo costo para prevenir o reducir los problemas de salud mental infantil en tres países de ingresos medios del Sudeste de Europa. Este pequeño estudio piloto previo y posterior está fundamentado por el marco de Alcance, Eficacia, Adopción, Implementación y Mantenimiento (RE‐AIM, por sus siglas en inglés) y evaluó la viabilidad de los procedimientos de intervención, de implementación y de evaluación: Fase 1 de la Estrategia de Optimización Multifase (MOST) de tres fases para la adaptación del programa. Un grupo de moderadores locales impartió el programa Crianza para la Salud Durante Toda la Vida (Parenting for Lifelong Health, PLH) para Niños Pequeños a padres de niños de entre 2 y 9 años en Macedonia del Norte, República de Moldavia, y Rumania en 2018. Los padres completaron evaluaciones antes y después del programa. Los resultados demostraron cambios positivos después del programa para las familias participantes (N = 140) en varias respuestas, entre ellas, los síntomas de exteriorización y de interiorización de los niños y la conducta de crianza, en los tres países, todos en la dirección esperada. La participación en el programa estuvo asociada con resultados positivos en las familias participantes. Sobre la base de las experiencias de este estudio piloto, describimos las consecuencias prácticas para la implementación satisfactoria de los programas de crianza en los tres países que servirán como base para las fases de nuestro próximo estudio, del experimento factorial y del ensayo controlado aleatorizado.